PENGETAHUAN IBU TENTANG PEMBERIAN IMUNISASI DI PUSKESMAS PERAWATAN LAWE SUMUR TAHUN 2019 - TJUT ALINI (LP2MTBM MAKARIOZ, 2019)
Complete basic immunization coverage for children aged 12-23 months for Aceh Province in 2018 has not met the target of 93% because there are still 20% coverage of basic immunization that has not been met (Renstra, 2019). The 2019 Strategic Plan target of 93% is still found in children aged 12-23 months in 2018 of 32.9%. This research is descriptive. The population in this study were 34 people and all of them were sampled. The data used are primary data (questionnaire). Data are analyzed and presented in frequency tables and cross tables.Based on the results of the study showed that the majority of respondents lack knowledge (58.9%), and a minority of well-informed 6 people (17.6%). Knowledge based on age, the majority of mothers aged 20-35 years and good knowledge (41.2%). Knowledge based on education level, the majority of mothers have basic education and lack knowledge (32.3%). Knowledge is based on parity, the majority of mothers are multiparous parity and have sufficient knowledge (29.5%). Knowledge based on information sources, the majority of mothers get information from the environment and lack knowledge (94.4%).It is expected that health workers in the District of Lawe Sumur can provide counseling and information about DPT immunization to mothers who have babies.